Nonhomologous DNA End Joining in Cell-Free Extracts - Sheetal Sharma; Sathees C. Raghavan (Journal of Nucleic Acids)
Among various DNA damages, double-strand breaks (DSBs) are considered as most deleterious, as they may lead to chromosomal rearrangements and cancer when unrepaired. Nonhomologous DNA end joining (NHEJ) is one of the major DSB repair pathways in higher organisms. A large number of studies on NHEJ are based on in vitro systems using cell-free extracts. In this paper, we summarize the studies on NHEJ performed by various groups in different cell-free repair systems.